IMPROVING STUDENTS’S READING COMPREHENSION TOWARD MIND MAPPING IN TERMS OF NARATIVE TEXT - herman (PENA : Jurnal Pendidikan Bahasa, Sastra, & Pengajaran, 2023)
The object of this study is to find out the implement of using mind mapping techniques to improve students’ reading comprehension in narrative texts. The data were gathered through test which were delivered into the pre-test and post-test. Based on the result of the research showed that mind mapping technique is improve students’ reading comprehension in narrative text, because the value of gained score (20.77) is higher than the control class (10.77). From the result of statistic hypothesis, has significance value 0.001. Based on the significance table is 0.05, meanings that 0.05 > 0.001. In other word the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. Therefore, teaching reading comprehension of narrative text has improves through mind mapping technique.